2006
DOI: 10.1136/jcp.2005.027839
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behavioural interpretation of cervical intraepithelial neoplasia with molecular biomarkers

Abstract: The microscopic phenotype of cervical intraepithelial neoplasia (CIN) reflects a fine balance between factors that promote or reduce CIN development. A shortcoming of the current grading system is its reliance on static morphology and microscopic haematoxylin-eosin features of the epithelium alone. In reality, CIN is a dynamic process, and the epithelium may exhibit differing results over time. Functional biomarkers p16, Ki-67, p53, retinoblastoma protein cytokeratin (CK)14 and CK13, help in the assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 92 publications
4
76
0
8
Order By: Relevance
“…[5][6][7] Investigators have proposed that the use of these and other biomarkers can help identify which lowergrade lesions will progress over time. 8,9 For example, in a study examining p16, Negri et al 10 reported that CIN1 cases with diffuse p16 staining had a significantly higher tendency to progress to a highgrade lesion than p16-negative cases. Hence, they recommended p16 as a useful surrogate marker for progression likelihood.…”
mentioning
confidence: 99%
“…[5][6][7] Investigators have proposed that the use of these and other biomarkers can help identify which lowergrade lesions will progress over time. 8,9 For example, in a study examining p16, Negri et al 10 reported that CIN1 cases with diffuse p16 staining had a significantly higher tendency to progress to a highgrade lesion than p16-negative cases. Hence, they recommended p16 as a useful surrogate marker for progression likelihood.…”
mentioning
confidence: 99%
“…6 Moreover, in two independent studies, adjuvant chemotherapy was significantly beneficial for patients with rapidly proliferating tumors, but not for patients with slowly proliferating tumors. 7,8 A comparison between phosphohistone H3/mitotic activity index and gene signatures, however, has not yet been performed.…”
mentioning
confidence: 99%
“…It is believed that biomarkers such as p16 can help in evaluating the likelihood for progression and regression in a particular CIN. 7 Such markers may be particularly useful in assisting triage of patients with borderline smears reported as ASC-US. Our study on an Asian screening population in Hong Kong showed that, similar to other screening populations, ASC-US is the most common abnormal cytologic finding 2 and is associated with a significantly higher chance to develop cervical cancer and its high-grade precursors.…”
Section: Correlation With Progress Of Diseasementioning
confidence: 99%
“…5,6 Although HPV test shows high sensitivity, additional markers are necessary to improve the specificity of identifying cervical cancers or high-grade precursors. [7][8][9][10][11] It is also necessary to discover adjunct markers for management of LSIL as HPV testing is not so effective in triage management of LSIL. …”
mentioning
confidence: 99%